Annual Plan 2001-2002 Volume II Scheme Wise Plan Outlay National Capital Territory of Delhi - Planning Commission (Planning Commission, 2001)
Health of the people is not only a desirable goal but also an essential investment Human resources. The National Health Policy reiterated’ India’s Commitment to attain For All (HFA) by 2000 AD. Primary health care has been accepted as the mam instrumental achieving this goal. Accordingly, a vast network of health care facilities in all areas & location of this Territory have been established
Planning Department, Government of National Capital Territory of Delhi